Overall Survival and Functional Results of Prostate-Sparing Cystectomy: A Matched Case-Control Study - Basiri, Abbas; Pakmanesh, Hamid; Tabibi, Ali; Radfar, Mohammad Hadi; Tajalli, Farzam; Ahadi, Babak; Eslami, Nazanin (Urology Journal, 2012)
PURPOSE: To compare two matched groups of men with bladder transitional cell carcinoma (TCC) who underwent prostate-sparing cystectomy (PSC) or conventional radical cystoprostatectomy (CRC). MATERIALS AND METHODS: Twenty-three men who have undergone PSC with the diagnosis of bladder TCC (Ta–T2) from 2003 to 2008 in Tehran, Iran were included in the study as the experimental group. The control group composed of 27 men with comparable tumor characteristics and age range, who had non-nerve-sparing radical cystoprostatectomy and orthotopic ileal W pouch reconstruction in the same center. All the procedures were performed by the same surgical group under the supervision of different attending staff. RESULTS: Mean follow-up period was 39 months in PSC and 35 months in CRC group. The 5-year overall survival was 47% and 30% in PSC and CRC groups, respectively. Median survival was 48 months in PSC and 36 months in CRC group, using Kaplan-Meier survival analysis (P> .05). Impotence was observed in 16.6% in PSC and in 83.3% in CRC group (P = .002). Mean International Index of Erectile Function-5 score of the PSC group was 19.8 compared with 5.7 in the CRC group (P = .003). Only one patient in each group was completely incontinent. Urethral anastomosis stricture occurred in 2 patients in CRC group. CONCLUSION: Patients who underwent PSC did not show decreased overall survival compared to CRC, which provided better functional results.